Processos geodinâmicos associados a mudanças de uso da terra: o caso da microbacia hidrográfica do Córrego Caçula (Ilha Solteira - SP) - Marteli, Alice Nardoni [UNESP] (2015)
Floods and flooding are increasingly common events in Brazilian urban centers as a result of land use and more frequent extreme weather events process. This situation is repeated in the Caçula Stream Watershed located in Ilha Solteira city (SP). One way to reduce the occurrence of such events and the damage associated with them is to know the natural taxes that interfere processes and their interaction temporal-spatial. Despite already covered by federal and state legal instruments in the study of urban risks, such an approach may be limited in small municipalities by the low availability of technical and financial resources for such studies. The development of alternatives to the characterization of water dynamics in the areas associated with data from previous geological and geotechnical conditions of the land and changing patterns of land use can accelerate the analysis process, allowing the identification of the most critical areas and interventions to harm reduction. Considering these conditions, the project proposed to use the LCM (Land Change Modeler) module of GIS Idrisi Selva in identifying land use and cover changes, and predict the areas with strong natural susceptibility to the occurrence of floods through the incorporation the HAND (Height Above the Nearest Drainage) algorithm. With the land use and cover change over the years 1975-2014, it was possible to identify the changes in the watershed and by associating HAND modeling. It was obtained the delimitation of areas with strong susceptibility to floods and flooding. Thus, the adapted approach enabled us to understand the dynamics of surface processes, define critical areas and hierarchize them for intervention purposes